2018
DOI: 10.1177/0956462418791946
|View full text |Cite
|
Sign up to set email alerts
|

Participant satisfaction with clinical trial experience and post-trial transitioning to HIV care in Kenya

Abstract: We conducted an exploratory analysis of former HIV Prevention Trials Network 052 (HPTN 052) clinical trial participants in 2016 to assess their (1) satisfaction with the HPTN 052 clinical trial care and treatment, and reasons for joining the trial; and (2) perspectives about the post-trial transition to public HIV care centers. Quantitative data showed that, of the 70 survey participants, 94.3% (n = 66) reported being very satisfied with the care and treatment they received while participating in the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
(28 reference statements)
0
17
0
2
Order By: Relevance
“…Continuity of care after trial closure requires that there are appropriate processes in place to support trial participants to be linked to alternative facilities (Odero et al, 2018). In HIV and other chronic disease research, appropriate linkage to care is important, given the potential negative consequences of treatment interruptions or treatment failure (Odero et al, 2018). Participants in the current study reported using referral for linking participants to post-trial care which they considered passive and unreliable in facilitating successful linkage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuity of care after trial closure requires that there are appropriate processes in place to support trial participants to be linked to alternative facilities (Odero et al, 2018). In HIV and other chronic disease research, appropriate linkage to care is important, given the potential negative consequences of treatment interruptions or treatment failure (Odero et al, 2018). Participants in the current study reported using referral for linking participants to post-trial care which they considered passive and unreliable in facilitating successful linkage.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that post-trial follow up and monitoring was rarely achieved. It is advised to have plans for follow up and monitoring incorporated in the entire research protocol (Odero et al, 2018). Moreover, to enable standardisation of post-trial care among researchers, post-trial care guidelines should be incorporated in research ethics policies and enforced by the ethical authorities (Lawton et al, 2019; Pratt, Paul, Hyder, & Ali, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The trial-closure phase highlights the main fears and concerns of trial participants associated with leaving trial-related healthcare and finding suitable alternatives. The psychological concerns that arise within the trial-closure phase mainly relate to the loss of the quality care(8) in research related facilities which cannot be matched with that in the public sector. (7) A recent systematic review similarly identified the loss of research-related care as a cause of stress among post-trial participants and that affects their integration into the public services.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have criticised existing trial guidance for its emphasis on generic and universalist principles that provide little detail on how to adapt and apply such principles into highly diverse local contexts. (6-8) There is a call to develop post-trial care guidelines that are flexible and sensitive to local contexts and to the specific needs of different groups of participants. In line with good research practice and with the principles of patient and public involvement,(9) such guidance should be developed collaboratively by a range of different stakeholders such as the government, researchers, communities, and research sponsors,(10, 11) and implemented in research practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation